PENGEMBANGAN BUKU PETUNJUK PRAKTIKUM KIMIA BERBASIS GREEN CHEMISTRY UNTUK SISWA SMA KELAS XI SEMESTER 2 - Fitria Rizkiana; Herlina Apriani; Yasmine Khairunnisa (UIN AR-RANIRY, 2020)
This study aimed to produce and test the feasibility of a laboratory guidebook based green chemistry for high school students. The type of this research was research and development using the 4-D model. The laboratory guidebook produced was assessed by two lecturers and three chemistry teachers. Data collection techniques used were nontest techniques in the form of questionnaires. The data obtained are used to analyze the feasibility of the content, presentation, language, graphics, and applicability of the green chemistry concept to the laboratory guidebook that has been produced. Analysis of the results of the assessment showed that the laboratory guidebook based green chemistry was considered to be very feasible on four aspects namely content, presentation, language and graphics, and was judged to be feasible on the applied aspects of the green chemistry concept.